Fra-2 Is a Dominant Negative Regulator of Natural Killer Cell Development - Schnoegl, Diana; Hochgerner, Mathias; Gotthardt, Dagmar; Marsh, Leigh M. (Frontiers in Immunology, 2022)
Natural killer (NK) cells play an important role in recognizing and killing pathogen-infected or malignant cells. Changes in their numbers or activation can contribute to several diseases and pathologies including systemic sclerosis (SSc), an autoimmune disease characterized by inflammation and tissue remodeling. In these patients, increased expression of the AP-1 transcription factor, Fra-2 was reported. In mice ectopic overexpression of Fra-2 (TG) leads to SSc with strong pulmonary fibrosis, pulmonary hypertension, and inflammation. Analysis of the underlying immune cell profile in the lungs of young TG mice, which do not yet show any signs of lung disease, revealed increased numbers of eosinophils and T cells but strongly reduced NK numbers. Therefore, we aimed to identify the cause of the absence of NK cells in the lungs of these mice and to determine the potential role of Fra-2 in NK development. Examination of inflammatory cell distribution in TG mice revealed similar NK deficiencies in the spleen, blood, and bone marrow. Deeper analysis of the WT and TG bone marrow revealed a potential NK cell developmental defect beginning at the preNKP stage. To determine whether this defect was cell-intrinsic or extrinsic, mixed bone marrow chimera and in vitro differentiation experiments were performed. Both experiments showed that the defect caused by Fra-2 was primarily cell-intrinsic and minimally dependent on the environment. Closer examination of surface markers and transcription factors required for NK development, revealed the expected receptor distribution but changes in transcription factor expression. We found a significant reduction in Nfil3, which is essential for the transition of common lymphoid cells to NK committed precursor cells and an AP-1 binding site in the promotor of this gene. In Summary, our data demonstrates that regulation of Fra-2 is essential for NK development and maturation, and suggests that the early NK dysfunction plays an important role in the pathogenesis of systemic sclerosis.